Asia's Experience in the Quest for a Regional Human Rights Mechanism - Chiam, Sou (Victoria University of Wellington Law Review, 2009)
The article outlines the development of a regional human rights charter in Asia. The article provides an historical overview of the efforts made to establish a charter, concluding that after fourteen UN workshops Asia still has not established any human rights mechanism. However, the author notes that some encouraging progress has been made. The article also identifies factors present in Asia that have hindered progress in establishing a regional mechanism and concludes with an outlook on how to proceed.